PENYULUHAN TENTANG UPAYA PENCEGAHAN PENYEBARAN COVID-19 KEPADA MASYARAKAT DI PUSKESMAS REJOSARI KECAMATAN TENAYAN RAYA TAHUN 2021 - Abdul Zaky; Marido Bisra; Sandya Bunga Prathivi; T.Mohd Yoshandi (LPPM Universitas Awal Bros, 2021)
People activities have changed by the emergence of the Covid-19 outbreak which continues to increase. The public's lack of understanding of the Covid-19 Virus and efforts to prevent the spread of Covid-19 is the duty of educators to provide education to the people. In this article, the author describes people activities that have been carried out to increase public understanding about Covid-19. People activities carried out at the Rejosari Health Center, Tenayan Raya District used the method of distributing brochures, lectures, discussions and questions and answers. For the results of this people activity, the people has understood the efforts that can be taken to prevent the spread of Covid-19, one of which is by implementing health protocols. The implementation of this activity is also a form of support for the Pekanbaru mayor's regulation Number 104 of 2020 regarding guidelines for new productive and safe people's living behavior in preventing and controlling the 2019 corona virus disease. This activity can also increase public awareness in maintaining personal hygiene and the environment.